Diffusion, implementation, and use of Research Electronic Data Capture (REDCap) in the Veterans Health Administration (VA). Issue 3 (11th June 2019) - Paris, Bonnie L; Hynes, Denise M
Abstract: This case study describes the implementation of the Research Electronic Data Capture (REDCap) software at the United States Department of Veterans Affairs Veterans Health Administration (VA). VA REDCap enables secure and standardized data collection, fosters collaboration with external researchers through use of a widely used data management tool, facilitates multisite studies through use of data forms that can be shared across sites within and outside the VA, is well suited to health services research studies and quality improvement projects, and enables exporting data for analysis in the VA secure computing environment. Using a diffusion of innovation framework approach, authors explore organizational factors that shaped adoption of REDCap technology and constraints on its use within the VA. Lessons learned from the VA experience are discussed.